Area Characteristics and Consumer Nutrition Environments in Restaurants: an Examination of Hispanic Caribbean Restaurants in New York City - Fuster, Melissa (J Racial Ethn Health Disparities, 2021)
Hispanics in the USA, particularly those of Caribbean descent, experience high levels of diet-related diseases and dietary risk factors. Restaurants are an increasingly important yet understudied source of food and may present opportunities to positively influence urban food environments. We sought to explore food environments further, by examining the association between neighborhood characteristics and restaurant consumer nutrition environments within New York City’s Hispanic Caribbean (HC) restaurant environments. We applied an adapted version of the Nutrition Environment Measurements Survey for Restaurants (NEMS-R) to evaluate a random sample of HC restaurants (n=89). NEMS-HCR scores (continuous and categorized as low, medium, and high based on data distribution) were examined against area sociodemographic characteristics using bivariate and logistic regression analysis. HC restaurants located in Hispanic geographic enclaves had a higher proportion of fried menu items (p<0.01) but presented fewer environmental barriers to healthy eating, compared with those in areas with lower Hispanic concentrations. No significant differences in NEMS-R scores were found by other neighborhood characteristics. Size was the only significant factor predicting high NEMS-HCR scores, where small restaurants were less likely to have scores in the high category (NEMS-HCR score>6), compared with their medium (aOR: 6.6, 95% CI: 1.8–24.6) and large counterparts (aOR: 5.6, 95% CI: 1.5–21.4). This research is the first to examine the association between restaurant location and consumer nutrition environments, providing information to contribute to future interventions and policies seeking to improve urban food environments in communities disproportionately affected by diet-related conditions, as in the case of HC communities in New York City.